Data Security and Individual Privacy from the Perspective of Public Administration - Sari, Jayanti Armida; Yuliani, Isnaeni; Akadira, Tora; Sunarya, Amud; Ating, Rashid (Ilomata International Journal of Social Science, 2024)
The widespread use of Information and Communication Technology (ICT) has transformed social, economic, and everyday interactions, creating challenges in data security and individual privacy. This study explores aspects of data security and privacy within public administration in Indonesia, highlighting existing challenges, policies, and initiatives. The research methodology is a qualitative literature review encompassing journal articles, books, and research reports on data security and privacy. The findings indicate that cyber threats such as hacking, phishing, ransomware, and data breaches have led to financial losses, reputational damage, and privacy violations in Indonesia. The discussion of this research suggests that data security strategies, including security policies, encryption technology, firewalls, access controls, and risk management, are crucial for protecting sensitive information. Legislative measures, public awareness, and technological protection are necessary to balance technological benefits and the safety of individual rights, ensuring compliance with regulatory standards and enhancing public trust in government and organizations.